Is all of this right?
\(\displaystyle -dy + y = \ln(x - y) + x - dx\)
\(\displaystyle e^{-dy + y} = e^{\ln(x - y) + x - dx}\)
\(\displaystyle e^{-dy} * e^{ y} = x - y * e^{x} * e^{-dx}\)
\(\displaystyle e^{-dy} * e^{ y} - y = x - y - y * e^{x} * e^{-dx}\)
\(\displaystyle e^{-dy} * e^{ y} - y = x * e^{x} * e^{-dx}\)
\(\displaystyle \ln(e^{-dy}) * \ln( e^{ y}) - \ln(y) = \ln(x) * \ln(e^{x}) * \ln(e^{-dx})\)
\(\displaystyle -dy + y - \ln(y) = \ln(x) + x -dx\)
\(\displaystyle -dy + y = \ln(x - y) + x - dx\)
\(\displaystyle e^{-dy + y} = e^{\ln(x - y) + x - dx}\)
\(\displaystyle e^{-dy} * e^{ y} = x - y * e^{x} * e^{-dx}\)
\(\displaystyle e^{-dy} * e^{ y} - y = x - y - y * e^{x} * e^{-dx}\)
\(\displaystyle e^{-dy} * e^{ y} - y = x * e^{x} * e^{-dx}\)
\(\displaystyle \ln(e^{-dy}) * \ln( e^{ y}) - \ln(y) = \ln(x) * \ln(e^{x}) * \ln(e^{-dx})\)
\(\displaystyle -dy + y - \ln(y) = \ln(x) + x -dx\)